Pengaruh Perceived Usefulness, Perceived Ease of Use, dan Compatibility Lifestyle terhadap Intention to Use Fitur Social Commerce (Studi Pada Pengguna Media Sosial TikTok) - Dyan Erlyn Oktania; Tias Andarini Indarwati (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
Social media companies began to grow their business by innovating shopping features. This phenomenon is referred to as social commerce, which uses social media to promote and transact directly on social media. In 2022, social commerce trends are predicted to grow and account for 40% of total e-commerce transactions. This study examines the effect of perceived usefulness, perceived ease of use, and compatibility with lifestyle on purchase intention using the TikTok Shop features. This type of research is quantitative research with judgemental sampling methods. An online questionnaire with a Likert scale of 1-5 was distributed to 100 respondents via social media TikTok. Data analysis techniques use multiple linear regression tests with the help of IBM SPSS 20. The results showed that perceived usefulness, perceived ease of use, and compatibility with lifestyle had a significant and positive effect on the purchase intention. Based on the result, it is recommended that businesses that use TikTok Shop feature develop creative marketing strategies by paying attention to the usability, ease, and compatibility of the TikTok Shop features with the user's lifestyle to increase purchase intention.